Notes on Spice Plants in the Genus Zanthoxylum (Rutaceae) in Northern Thailand - Suksathan, Ratchuporn; Trisonthi, Chusie; Trisonthi, Paritat; Wangpakapattanawong, Prasit (Thai Forest Bulletin (Botany), 2014)
A survey of four spice plants in the genus Zanthoxylum L. (Rutaceae) was conducted in Northern Thailand: Ma-Maad (Zanthoxylum acanthopodium DC.), Hua-Jiao (Z. armatum DC.), Ma-Kwaen (Z. myriacanthum Wall. ex Hook. f.), and Ma-Kwuang (Z. rhetsa (Roxb.) DC.). The important characters, key to species based on morphological studies, and traditional usages of each species are provided. An interesting plant used for medicinal purpose is Z. armatum, the bark of which can be used for pain-relief of toothache. The morphological characters of the four Zanthoxylum species were compared and analyzed using principal components analysis (PCA). The results showed that the four Zanthoxylum species can be distinguished using leaf and flower characters. The stomatal index (I) was different among species. Anatomical data drawn from young stems show that dendritic crystals are present in the stems of Z. myriacanthum and Z. rhetsa.